(untitled) (El Taco en la Brea, 2025)
Through their contributions to a regional and decentralizing historiography of art and literature, Argentine dramaturgies from the Patagonia and Northwest regions allow us to recognize and study different representations of «historical alterities». Therefore, in this article we will analyze critical figurations of otherness read in terms of aporophobia. To carry out this inquiry, we organized a specific observational map, based on scenic «nodes» designed by plays from the northern and southern regions, in the period 1983‒2002. This dramaturgical cartography will provide different conceptual topics, historical images, stylistic procedures and aesthetic notions about the poetic corrosion of the aporophobic organized from these textualities.